2020
DOI: 10.1101/2020.09.26.314815
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictive Maps in Rats and Humans for Spatial Navigation

Abstract: Much of our understanding of navigation has come from the study of rats, humans and simulated artificial agents. To date little attempt has been made to integrate these approaches into a common framework to understand mechanisms that may be shared across mammals and the extent to which different instantiations of agents best capture mammalian navigation behaviour. Here, we report a comparison of rats, humans and reinforcement learning (RL) agents in a novel open-field navigation task (Tartarus Maze) requiring … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 157 publications
(374 reference statements)
2
25
0
Order By: Relevance
“…These findings and their implications for current models of place cells are discussed below. Cothi et al 2020). Extending these results, we found that rats were able to learn and remember the status of doors being locked or unlocked, in the absence of directly perceivable changes other than the direct feedback when pushing on a door.…”
Section: Discussionsupporting
confidence: 67%
“…These findings and their implications for current models of place cells are discussed below. Cothi et al 2020). Extending these results, we found that rats were able to learn and remember the status of doors being locked or unlocked, in the absence of directly perceivable changes other than the direct feedback when pushing on a door.…”
Section: Discussionsupporting
confidence: 67%
“…Rats and humans can flexibly adapt to changes in environmental connectivity. 13 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 Here, rats adapted to the locked or unlocked status of doors, even door sides, in the absence of directly perceivable changes. Importantly, their bias toward open doors persisted into the last session suggesting learning of connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the classic divisions of model-free and model-based literature in decision-making tasks, there are other families of RL algorithms that provide alternative accounts, including hierarchical RL, linear RL, and successor representation ( Botvinick et al, 2009 ; Dayan, 1993 ; Gershman, 2018 ; Piray and Daw, 2019 ; Russek et al, 2017 ; Stachenfeld et al, 2017 ; Tessereau et al, 2020 ). In particular, successor representation can account for flexible behaviour of rats and humans in complex mazes ( De Cothi et al, 2020 ) and humans in reward devaluation protocols ( Momennejad et al, 2017 ). Interestingly, components of the successor representation during simulations show similarities to properties of place cells and grid cells, including the influence of goal locations on place field over-representation observed in specific paradigms and influence of environmental geometry on grid field integrity ( Duvelle et al, 2019 ; Ekstrom et al, 2020 ; Krupic et al, 2015 ; Stachenfeld et al, 2017 ).…”
Section: How Might the Striatum Contribute To Flexible Navigation Behmentioning
confidence: 99%